2006
DOI: 10.1118/1.2350658
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theory of a solution space for the biplane imaging geometry problem

Abstract: Biplane angiographic imaging is a primary method for visual and quantitative assessment of the vasculature. In order to reliably reconstruct the three-dimensional (3D) position, orientation, and shape of the vessel structure, a key problem is to determine the rotation matrix R and the translation vector t which relate the two coordinate systems. This so-called Imaging Geometry Determination problem is well studied in the medical imaging and computer vision communities and a number of interesting approaches hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…From these initially identified image points, an initial estimate of the imaging geometry and the 3D data can be estimated first and then iteratively refined by optimization techniques. The effects of point configuration on the accuracy in 3D reconstruction from biplane image were investigated by Dmochowski et al 44 Recently, Singh et al 45 introduced the concept of a solution space of feasible geometries for biplane imaging geometry problems and showed that more than one solution might exist. Different from all these works, the present technique only uses a single projection image to determine the 3D structure of the pelvis, which was previously regarded by Metz and Fencil 41 as an imaging method that does not provide information concerning the object's 3D structure.…”
Section: Discussionmentioning
confidence: 99%
“…From these initially identified image points, an initial estimate of the imaging geometry and the 3D data can be estimated first and then iteratively refined by optimization techniques. The effects of point configuration on the accuracy in 3D reconstruction from biplane image were investigated by Dmochowski et al 44 Recently, Singh et al 45 introduced the concept of a solution space of feasible geometries for biplane imaging geometry problems and showed that more than one solution might exist. Different from all these works, the present technique only uses a single projection image to determine the 3D structure of the pelvis, which was previously regarded by Metz and Fencil 41 as an imaging method that does not provide information concerning the object's 3D structure.…”
Section: Discussionmentioning
confidence: 99%